Assessing the Problem-Solving Strategies of Linear Function Using Blended Learning: The Effectiveness of Educational Social Network - Almeida, Valdneide; Gomes, Alex Sandro; Spinilo, Alina; Saraiva, Juliana (Anais do Workshop de Informática na Escola (WIE); 2016: Anais do XXII Workshop de Informática na Escola, 2016)
Learning processes of Mathematics have been facing historical difficulties when the study object is an abstract issue such as Linear Function (LF). In this context, mixture approach for teaching has been adopted: Blended Learning (BL). Thus, the goal of this study is to assess problemsolving strategies concerning LF when a BL approach is applied. The methodological steps were composed by face-to-face observations, virtual observations, and questionnaire application. The research was conducted at a public school with 02 teachers and 84 students. As result, 08 learning strategies were identified, and it was possible to observe evidences of the effectiveness of the BL when it was adopted in the described context.